giải hộ minh
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,ĐK:x\ge0;x\ne4\\ A=\dfrac{\left(2\sqrt{x}+1\right)\left(\sqrt{x}-2\right)}{\sqrt{x}-2}=2\sqrt{x}+1\\ B=\dfrac{\left(x-1\right)\left(\sqrt{x}+2\right)}{\sqrt{x}+2}=x-1\\ b,M=A:B=\dfrac{2\sqrt{x}+1}{x-1}=\dfrac{2\left(\sqrt{x}+1\right)-1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\\ M=\dfrac{2}{\sqrt{x}-1}-\dfrac{1}{\sqrt{x}+1}\in Z\\ \Leftrightarrow\left\{{}\begin{matrix}\sqrt{x}-1\inƯ\left(2\right)=\left\{-2;-1;1;2\right\}\\\sqrt{x}+1\inƯ\left(1\right)=\left\{-1;1\right\}\end{matrix}\right.\\ \Leftrightarrow\left\{{}\begin{matrix}\sqrt{x}\in\left\{0;2;3\right\}\left(\sqrt{x}\ge0\right)\\\sqrt{x}=0\left(\sqrt{x}\ge0\right)\end{matrix}\right.\Leftrightarrow x=0\)
( 3x-1) ( x2+ 9) = (3x-1) (7x-10)
⇒( 3x-1) ( x2+ 9) - (3x-1) (7x-10) = 0
⇒( 3x-1) (( x2+ 9)-(7x-10)) = 0
⇒( 3x-1)(x2+9-7x+10)=0
⇒( 3x-1)(x2-7x+19)=0
⇒\(\left[{}\begin{matrix}3x-1=0\\x^2-7x+19=0\end{matrix}\right.\)
3x-1=0
⇒x=\(\dfrac{1}{3}\)
x2-7x+19=0
⇒ \(x^2-\dfrac{7}{2}x-\dfrac{7}{2}x+\left(\dfrac{7}{2}\right)^2+\dfrac{27}{4}=0\)
⇒ \(\left(x-\dfrac{7}{2}\right)^2+\dfrac{27}{4}=0\)
vì \(\left(x-\dfrac{7}{2}\right)^2\ge0\); \(\dfrac{27}{4}>0\)
⇒ \(\left(x-\dfrac{7}{2}\right)^2+\dfrac{27}{4}>0\)
⇒ x vô nghiệm
Vậy x= \(\dfrac{1}{3}\)
\(\left(3x-1\right)\left(x^2+9\right)=\left(3x-1\right)\left(7x-10\right)\\ \Leftrightarrow\left(3x-1\right)\left(x^2+9\right)-\left(3x-1\right)\left(7x-10\right)\\ \Leftrightarrow\left(3x-1\right)\left(x^2-7x+12\right)=0\\ \Leftrightarrow\left(3x-1\right)\left(x^2-4x-3x+12\right)=0\\ \Leftrightarrow\left(3x-1\right)\left[x\left(x-4\right)-3\left(x-4\right)\right]=0\\ \Leftrightarrow\left(3x-1\right)\left(x-3\right)\left(x-4\right)=0\\ \Leftrightarrow\left\{{}\begin{matrix}3x-1=0\\x-3=0\\x-4=0\end{matrix}\right.\\ \Leftrightarrow\left\{{}\begin{matrix}x=\dfrac{1}{3}\\x=3\\x=4\end{matrix}\right.\)
Chu vi vủa tấm tôn là:
(\(\dfrac{2}{3}\) + \(\dfrac{1}{4}\)) x 2 = \(\dfrac{11}{6}\) (m)
Đáp số: ...
\(11\times x-x=10\)
\(11\times x-1\times x=10\)
\(\left(11-1\right)\times x=10\)
\(10\times x=10\)
\(x=10:10\)
\(x=1\)
\(3^{15}-9^6=3^{15}-\left(3^2\right)^6=3^{15}-3^{12}=3^{12}\left(3^3-1\right)=3^{12}\cdot26=3^{12}\cdot13\cdot2⋮13\)